A Blind Signature-Aided Privacy-Preserving Power Request Scheme for Smart Grid. (1st July 2021) - Zhang, Weijian; Guo, Zhimin; Li, Nuannuan; Li, Mingyan; Fan, Qing; Luo, Min
Abstract : Smart grid is an emerging power system capable of providing appropriate electricity generation and distribution adjustments in the two-way communication mode. However, privacy preservation is a critical issue in the power request system since malicious adversaries could obtain users' daily schedule through power transmission channel. Blind signature is an effective method of hiding users' private information. In this paper, we propose an untraceable blind signature scheme under the reputable modification digital signature algorithm (MDSA). Moreover, we put forward an improved credential-based power request system architecture integrated with the proposed blind signature. In addition, we prove our blind signature's blindness and unforgeability under the assumption of Elliptic Curve Discrete Logarithm Problem (ECDLP). Meanwhile, we analyze privacy preservation, unforgeability, untraceability, and verifiability of the proposed scheme. Computational cost analysis demonstrates that our scheme has better efficiency compared with other two blind signatures.